Eficiencia del carbón activado (CA) procedente de los residuos de bambú (Bambusa vulgaris) para remoción de contaminante del agua - Loor Reyes, Génesis Jamileth (2024)
The objective of this research is to evaluate the efficacy of activated carbon from Bamboo (Bambusa vulgaris) waste for the removal of water pollutants, under a DCA with 12 experimental units; having as objectives: Obtaining activated carbon from Bamboo waste, determining the most efficient treatment and elaborating an economic analysis of the most efficient one. The total bamboo residue in activated carbon was 99.3% (7115 g) and 0.70% (50 g) of ash. Initially, the river water presented a turbidity of 19.69 mg/l, pH 7.7 mg/l, T 23.1°C, hardness 150 mg/l, color 179 PT-CO, sulfate 60 mg/l, nitrite 2.27, nitrate 25 mg/l, phosphate 8.1 mg/l, sst 164 mg/l, absorption cap 121.41 mg/g per 5g of AC. With the analysis of variance it was determined that there is significance between the types of filters, highlighting the forced filtration, where the turbidity in T2 was 6.2 mg/l; the TDS in T3 with 158.3 mg/l; the pH remained between 7.1 and 6.1; in T4 hardness was 142.8 mg/l; color T2 with 33.67 PT-CO; sulfate obtained 146.3 mg/l in T3; nitrites 0.47 in T3; nitrates 0.036 mg/l in T3; phosphates was better in T2 (fast filtration) but did not comply with environmental regulations; TSS presented 0.04 mg/l in T3. In conclusion, T2 with forced filtration presented a more efficient removal rate of 64.09%, fulfilling the alternative hypothesis, requiring 50 g of activated carbon, and the total cost of manufacturing the filter was $535.4.